STRATEGI PEMBELAJARAN SENI TARI DI SMP NEGERI 5 KERINCI KECAMATAN SIULAK MUKAI KABUPATEN KERINCI - Dara Ardilla; Indrayuda Indrayuda; Fuji Astuti (SENDRATASIK UNP, 2017)
AbstractThis article the aim  of the explain was to find out and describe the students’ learning activities at dance and teachers strategy in the learning process for 8th grade student at SMP Negeri 5 Kerinci Kecamatan Siulak Mukai. This was a qualitative research by using descriptive methods. The object of the research owas the strategy that the teacher used in dance lesson for 8th grade students with a total amount of students was 17, consists of 9 boys and 8 girls. The researcher was the primary instrument in the research by directly observed the learning process of the dance at 8th SMP Negeri 5 Kerinci Kecamatan Siulak Mukai. The collection of the data were a library research, observation, documentation, and an interview. The result of the research shows that the learning process of the dance at 8th grade SMP Negeri 5 Kerinci Kecamatan Siulak Mukai has not reach a maximum result of the learning process. The teacher has not properly use the strategy of teaching. Moreover, the teacher methods and the materials is not interesting. Teacher only uses LKS (Student’s Book Work) in the learning process. As the result, the student is deficient motivation and the learning process is monotonous. These problems impact towards students learning result, where the lowest KKM (minimum indicator score) at 75,00, but the average score of the students at 8th grade is 73,52 or below the minimum indicator score.Keywords: Strategy, Learning, Dance.